French Endocrine Society Guidance on endocrine side effects of immunotherapy. Issue 2 (February 2019) - Castinetti, F; Albarel, F; Archambeaud, F; Bertherat, J; Bouillet, B; Buffier, P; Briet, C; Cariou, B; Caron, Ph; Chabre, O; Chanson, Ph; Cortet, C; et al.
Abstract : The management of cancer patients has changed due to the considerably more frequent use of immune checkpoint inhibitors (ICPIs). However, the use of ICPI has a risk of side effects, particularly endocrine toxicity. Since the indications for ICPI are constantly expanding due to their efficacy, it is important that endocrinologists and oncologists know how to look for this type of toxicity and how to treat it when it arises. In view of this, the French Endocrine Society initiated the formulation of a consensus document on ICPI-related endocrine toxicity. In this paper, we will introduce data on the general pathophysiology of endocrine toxicity, and we will then outline expert opinion focusing primarily on methods for screening, management and monitoring for endocrine side effects in patients treated by ICPI. We will then look in turn at endocrinopathies that are induced by ICPI including dysthyroidism, hypophysitis, primary adrenal insufficiency and fulminant diabetes. In each chapter, expert opinion will be given on the diagnosis, management and monitoring for each complication. These expert opinions will also discuss the methodology for categorizing these side effects in oncology using 'common terminology criteria for adverse events' (CTCAE) and the difficulties in applying this to endocrine side effects in the case of these anti-cancer therapies. This is shown in particular by certain recommendations that are used for other side effects (high-dose corticosteroids, contraindicated in ICPI for example) and that cannot be considered as appropriate in the management of endocrine toxicity, as it usually does not require ICPI withdrawal or high-dose glucocorticoid intake.